1977
DOI: 10.1038/bjc.1977.113
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage carcinogenesis with rat embryo cells in tissue culture

Abstract: Summary.-Transformation of rat embryo fibroblasts in vitro has been investigated using initiation with either benzo(a)pyrene (BaP), 7,12-dimethylbenz(a)anthracene (DMBA) or benzo(e)pyrene (BeP) and promotion with either phorbol ester (TPA) or croton oil (Cr.Oil). The criteria used to assess in vitro transformation were (a) the efficiency of cloning in liquid medium, (b) abnormal cellular morphology and (c) the development of malignant tumours following s.c. inoculation of newborn rats.The results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…In contrast to our observations, others have shown that when TPA was applied 3-5 days after carcinogen treatment in mouse cells or 7 days after carcinogen treatment in rat cells (Lasne et al, 1977) or rat cells (Lasne et al, 1977 Morphological changes appeared to reflect the initial events in transformation that are followed later by tumorigenesis and growth in soft agar. The studies reported here indicate that cells become tumorigenic before they acquire the ability to grow in soft agar (Tables I and II).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our observations, others have shown that when TPA was applied 3-5 days after carcinogen treatment in mouse cells or 7 days after carcinogen treatment in rat cells (Lasne et al, 1977) or rat cells (Lasne et al, 1977 Morphological changes appeared to reflect the initial events in transformation that are followed later by tumorigenesis and growth in soft agar. The studies reported here indicate that cells become tumorigenic before they acquire the ability to grow in soft agar (Tables I and II).…”
Section: Discussioncontrasting
confidence: 99%
“…In vitro effects of 12-0-tetradecanoyl-phorbol-13-acetate (TPA) on cellular multiplication, RNA synthesis and DNA repair synthesis have been studied in mouse fibroblasts (Sivak & Van Duuren, 1970;Sivak et al, 1969Sivak et al, , 1972Trosko et al, 1975). More recently, TPA has been shown to enhance the focal transformation rate of mouse C3H/1OT1/2 cells and to enhance transformation in rat fibroblasts in culture (Lasne et al, 1974(Lasne et al, , 1977. The rate of focal transformation in mouse cells could be increased or decreased, depending * To whom requests for reprints should be sent. on the time at which TPA was administered relative to the carcinogen .…”
mentioning
confidence: 99%
“…Although BP carcinogenicity involves initial DNA damage, tumorigenicity is greatly enhanced by tumor promoters [11, 12], which interfere with these protective events [42, 43]. Cell cycle arrest gives cells time to repair DNA damage; apoptosis (programmed cell death) eliminates severely damaged cells.…”
Section: Introductionmentioning
confidence: 99%
“…This acquisition of'immortality' might be the only indication, over quite a long period of time in tissue culture, that some early events toward neoplas tic development had occurred. After extensive propagation in tissue culture, karyotypes may become unstable and cells may irreversibly acquire some or all transformation characteristics, including even that of tumor formation [15,16]. Thus, from an operational point of view, events leading to "immortalisation' might be considered as one type of "initiation" [ 17.…”
Section: Introductionmentioning
confidence: 99%